1998
DOI: 10.1111/j.1944-8287.1998.tb00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Migration and Remittances for Mexican Transnational Communities*

Abstract: To better understand the positive contributions return migrants and migrant remittances make in Latin American society, this paper offers a reevaluation of existing conceptual frameworks. Previous research dwelt upon the unproductive nature of expenditures and the difficulties facing return migrants as they reintegrate themselves in home communities, among other problems caused by migration. Drawing upon recent feminist scholarship and the growing body of literature focused on the positive aspects of "migradol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 31 publications
0
42
0
6
Order By: Relevance
“…Lindley's (2009) research on the Somali diaspora in London showed a reordering of a traditional patriarchal society through the feminization of income earning and remittance sending. Other scholars have looked at the migrant-sending context, in which the long-term absence of male remitters results in remittance-receiving wives gaining decision-making power over the use of remittances and the management of the household economy (Conway and Cohen 1998). The case of Ghanaian women in Toronto (Wong 2006) exemplifies the gendered politics of remittances among shifting transnational families: women's matrilineal power is strengthened by female-to-female remittances, although not without contestations from male relatives.…”
Section: A Gender Agenda For the Study Of Remittancesmentioning
confidence: 99%
“…Lindley's (2009) research on the Somali diaspora in London showed a reordering of a traditional patriarchal society through the feminization of income earning and remittance sending. Other scholars have looked at the migrant-sending context, in which the long-term absence of male remitters results in remittance-receiving wives gaining decision-making power over the use of remittances and the management of the household economy (Conway and Cohen 1998). The case of Ghanaian women in Toronto (Wong 2006) exemplifies the gendered politics of remittances among shifting transnational families: women's matrilineal power is strengthened by female-to-female remittances, although not without contestations from male relatives.…”
Section: A Gender Agenda For the Study Of Remittancesmentioning
confidence: 99%
“…Indeed, the earliest work in this field was based on the significance of hometown associations in both maintaining links across national territories but also in transforming migrant origin spaces (Basch et al 1994). Key to such transformative effects are the very large flows of remittances through formal (Conway and Cohen 1998) and informal (Rahman and Yeoh 2006) transnational financial spaces, which, globally, are currently estimated at US$ 232 billion annually (United Nations 2006). With reference to Guatemala, Taylor et al (2006) have illustrated how remittances have led to dramatic changes in rural landscapes as migrants' families convert land from rainforest to agricultural uses.…”
Section: New Spatialities Of Transnationalismmentioning
confidence: 99%
“…There is a need to extend the scope of these studies to investigate the social experiences of remittances, particularly at the family and household scales. Work that incorporates a gendered perspective focuses more on remittance behaviors and activities from two viewpoints-those of the migrants who remit or those of the family members who receive the moneyand less on the constructed and dialectic processes that remittances entail (Blue 2004;Conway and Cohen 1998;de la Brière, Sadoulet, de Janvry, and Lambert 2002;Goldring 2002). Notable exceptions include the work of Asis, Huang, and Yeoh (2004); Levitt (2001);and Parreñas (2001).…”
Section: Transnationalism and Remittancesmentioning
confidence: 99%
“…Intense scholarly attention is focusing on remittances at a time of profound international and national interest in their potential for reducing poverty in developing countries (Adams and Page 2005;Blue 2004; Cotula and Toulmin 2004;Conway and Cohen 1998;Guarnizo 2003;Sana and Massey 2005;Vertovec 2004). Exceeding $126 billion in (World Bank 2005, remittances are an important part of global financial flows and constitute critical sources of income for the households and economies of these countries.…”
mentioning
confidence: 99%